Development Of Hybrid Organic-Inorganic Hydride For Reversible Hydrogen Storage - Tan, Khai Chen (2020)
Storing hydrogen efficiently in condensed materials is a key technical challenge. Tremendous efforts have been given to inorganic hydrides containing B-H, Al-H and/or N-H bonds, while organic compounds with a great variety and rich chemistry in manupulating C-H and unsaturated bonds, however, are undervalued mainly because of their unfavourable thermodynamics and selectivity in dehydrogenation. Here, we developed a new family of hydrogen storage material spanning across the domain of inorganic and organic hydrogenous compounds, namely metallo-N-heterocycles, utilizing the electron donating nature of alkali or alkaline earth metals to tune the strengths of C-H, C-N and C-C bonds of N-heterocyclic molecules to be suitable for hydrogen storage in terms of thermodynamic and kinetic properties.